Cry of curs : language, class and the mob in Sidney, Spenser and Shakespeare - Zirbel, Jason J. (My University, 2009)
According to Stephen Greenblatt, "the Renaissance displays a markedly increased sensitivity, nourished by classicism, to theoretical implications of genre differentiation." In the works of Sidney, Spenser, and Shakespeare, the respective genres of pastoral romance, chivalric romance, and history stage play each work to advance the individual class interest of the author. In Book 2 of the Old and New Arcadia, the aristocratic Sidney depicts upper-class characters as possessing a linguistic facility which allows and at times justifies their manipulation of the inherently inarticulate lower-class mob. In Book 5 canto 2 of Spenser's Faerie Queene, the knight Artegall acts as an enforcer of centralized authority, deconstructing the populist ideology of a demagogic giant, and recalling the bureaucratic Spe~ser's own fear of the unrestrained voice of the lower orders as laid out in his View ofthe Present State of Ireland. Finally, the Roman history play Coriolanus allows Shakespeare to demonstrate the importance of language and roleplaying in the social and political arenas, thereby legitimating the occupation by which he earned the financial capital that allowed him to lay claim to the title of gentleman. The humanistic belief in the power of language to shape social reality is evident in the work of each author, as is influence of the class society that formed the ideology underlying each text.
A Thesis Submitted in Partial Fulfillment of the Requirements for the Degree of Master of Arts - English --University of Wisconsin-Oshkosh, 2008
Keywords: Sidney, Philip; Shakespeare, William; Spenser, Edmund; Politics and literature -- Great Britain -- History; Speech and social status -- England; English literature -- Early modern, 1500-1700, History and criticism